2001
DOI: 10.1172/jci200111494
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells play a key role in neutrophil recruitment in experimental bullous pemphigoid

Abstract: IntroductionBullous pemphigoid (BP) is an acquired autoimmune skin disease characterized by autoantibodies against two hemidesmosomal antigens, BP230 (BPAG1) and BP180 (BPAG2), and subepidermal blisters (1). These antihemidesmosomal autoantibodies can be detected, along with complement proteins, bound to the dermal-epidermal junction (DEJ) of perilesional skin. In the skin lesions of these patients, basal keratinocytes detach from the underlying dermis at the level of the lamina lucida, leading to subepidermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 43 publications
(33 reference statements)
3
91
2
2
Order By: Relevance
“…We have previously shown that anti-mBP180-mediated complement activation is essential for PMN recruitment to the cutaneous BMZ (37,38). One finding that demonstrated this link is that C5 -/-mice injected i.d.…”
Section: Figurementioning
confidence: 96%
See 4 more Smart Citations
“…We have previously shown that anti-mBP180-mediated complement activation is essential for PMN recruitment to the cutaneous BMZ (37,38). One finding that demonstrated this link is that C5 -/-mice injected i.d.…”
Section: Figurementioning
confidence: 96%
“…with the suboptimal and optimal doses of pathogenic IgG and examined at 2, 12, 24, and 48 hours after injection. At 2 hours, when MC degranulation triggered by pathogenic IgG reaches its peak (38), toluidine blue staining revealed extensive MC degranulation in the dermis of WT and Fb -/-mice ( Figure 4, A and C). In contrast, C4 -/-mice exhibited a minimal level of MC degranulation in the dermis ( Figure 4B).…”
Section: Pathogenic Anti-mbp180 Antibodies Induce Subepidermal Blistementioning
confidence: 99%
See 3 more Smart Citations